1995
DOI: 10.1051/rnd:19950504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate fat intake with different n-3 fatty acid sources and n-6/n-3 ratios on serum and structural lipids in rats

Abstract: Summary ― The aim of this study was to compare the effects of dietary polyunsaturated fatty acids (PUFA) on serum and membrane lipids in rats fed diets containing moderate levels of fats (6% by weight). Control rats received enough PUFA to prevent any deficiency. Experimental rats were fed linseed oil, salmon oil, or sunflower oil. After 8 weeks of feeding, fasting serum triacylglycerol and cholesterol levels were not altered in the linseed oil group. In contrast, in the salmon oil group, serum choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…lipids in PUFA in response to the inclusion of linseed oil and, to a lesser extent, fish oil, was most likely a result of replacing MUFA by PUFA. Similarly as in this paper (Table 5), Fremont (1995) also observed a negative correlation between PUFA and MUFA. The synthesis of endogenous monounsaturated fatty acids classified as MUFA increases under a deficit of PUFA.…”
Section: Discussionsupporting
confidence: 89%
“…lipids in PUFA in response to the inclusion of linseed oil and, to a lesser extent, fish oil, was most likely a result of replacing MUFA by PUFA. Similarly as in this paper (Table 5), Fremont (1995) also observed a negative correlation between PUFA and MUFA. The synthesis of endogenous monounsaturated fatty acids classified as MUFA increases under a deficit of PUFA.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to previous studies (Nelson et al 1997), we found that x-3 fatty acids had a lowering effect on plasma total-cholesterol and triglyceride concentrations. The cholesterol-HDL was also reduced, as reported by others in rodents (Fremont et al 1995). Because skeletal muscle is one of the most important organs involved in fatty acid metabolism in healthy humans it is very likely that it would be affected by the hypolipideamic properties of fish oil.…”
Section: Discussionsupporting
confidence: 75%
“…Increased incorporation of n-3 polyunsatu-rated fatty acids (n-3 PUFA) into tissues using a diet containing n-3 fatty acids has been demonstrated in rats (Fremont et al, 1995). The beneficial effect of n-3 PUFA is related to changes in the structure of membranes and to modulation of eicosanoid synthesis.…”
Section: Introductionmentioning
confidence: 99%